2014
DOI: 10.1002/acr.22389
|View full text |Cite
|
Sign up to set email alerts
|

Is Statin Use Associated With New Joint‐Related Symptoms, Physical Function, and Quality of Life? Results From Two Population‐Based Cohorts of Women

Abstract: Objective. Previous studies have suggested that statins may prevent development of osteoarthritis and have antiinflammatory effects. Our aim was to examine the associations between statin use and patient-reported joint symptoms in 2 large cohorts of middle-aged and older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
1
13
1
1
Order By: Relevance
“…29 The prevalence of knee osteoarthritis and the complaint of exhaustion were greater in statin users than in non-users, and those might be the risk factors of physical function decline. 23 If a patient complains of muscle symptoms, statin therapy might be discontinued, therefore, community-dwelling older statin users in the present study might have few complaints of SAMS. 21 It was considered that statin users in the present study had higher risks of SAMS than in the previous study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…29 The prevalence of knee osteoarthritis and the complaint of exhaustion were greater in statin users than in non-users, and those might be the risk factors of physical function decline. 23 If a patient complains of muscle symptoms, statin therapy might be discontinued, therefore, community-dwelling older statin users in the present study might have few complaints of SAMS. 21 It was considered that statin users in the present study had higher risks of SAMS than in the previous study.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, compared with another study, which reported physical function deterioration, statin users in the present study were slightly younger than the older group women were, had lower BMI, higher prevalence of diseases and seemed to have higher risks of SAMS. 23 If a patient complains of muscle symptoms, statin therapy might be discontinued, therefore, community-dwelling older statin users in the present study might have few complaints of SAMS. However, based on the result of the univariate analyses in this study, physical function appeared to be lower in statin users than non-users.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a randomized controlled trial study on 3022 post-menopausal women, oral administration of statins was neither capable to increase BMD nor prevent bone fractures [117]. Moreover, systemic administration of statins is associated with systemic side effects [45][46][47][48][49][50]. Local delivery of statins may be the alternative option which increases the bioavailability of the drugs and reduces the dose and dosage required for bone healing and the need for repeated administrations [6,118,119].…”
Section: Route Of Administrationmentioning
confidence: 99%